The Possible Protective Effect of Cinnamic Acid on Ovalbumin-Induced Asthma in Mice - Haidar AL-Saffar; Munaf H. Zalzala (College of Pharmacy University of Baghdad, 2023)
Asthma is a chronic respiratory disorder in which immunological and structural cells play a role. The limits of conventional medicines necessitate the development of innovative therapeutic techniques for asthma. In the present study, we investigated the possible protective effect of cinnamic acid (CA) on ovalbumin-induced asthma in a mouse model. Sixty albino male mice BALB/c type weighing (20-30) grams were chosen at random and divided into five groups each one contains 12 animal: Group I: PBS/liquid paraffin control. Group II: asthma model group. Group III: cinnamic acid control group; mice received cinnamic acid (50 mg/kg) in liquid paraffin orally by gavage. Group IV: asthma model / group of (25 mg / kg) cinnamic acid; mice received (25 mg/kg) in liquid paraffin orally by gavage. Group V:  asthma/ (50 mg/kg) cinnamic acid group; mice received cinnamic acid (50 mg/kg) in liquid paraffin orally by gavage. The experiment continued for 14 days. On day 15, broncho-alveolar lavage fluid, blood and lung tissue was collected. Total cell count, tissue TNF- α, IL -33, and serum IgE increased considerably after sensitization to ovalbumin (OVA), while GSH levels decreased significantly. On the other hand, administration of cinnamic acid in (25mg and 50mg/kg) has significantly decreased total WBC count, tissue TNF- α, IL -33, and serum IgE results, and a significant increase on GSH results. These findings suggest that cinnamic acid has a protective effect against OVA-induced allergic asthma in mice, possibly through its antioxidant activity and inhibitory activity on some proliferative modulating enzymes.